2015
DOI: 10.1099/jmm.0.077768-0
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antifungal activity and mechanism of essential oil from fennel (Foeniculum vulgare L.) on dermatophyte species

Abstract: Fennel seed essential oil (FSEO) is a plant-derived natural therapeutic against dermatophytes. In this study, the antifungal effects of FSEO were investigated from varied aspects, such as MIC and minimum fungicidal concentration, mycelia growth, spore germination and biomass. The results indicated that FSEO had potent antifungal activities on Trichophyton rubrum ATCC 40051, Trichophyton tonsurans 10-0400, Microsporum gypseum 44693-1 and Trichophyton mentagrophytes 10-0060, which is better than the commonly use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(35 citation statements)
references
References 38 publications
2
33
0
Order By: Relevance
“…Previous studies have shown a strong antagonistic activity of thyme essential oil against undesirable bacteria (Hosseini et al, 2009). However, it is shown that this is not the case with the fungus evaluated here, which could be explained due to when the thyme essential oil is mixed with Tween ® , then the antifungal capacity decreases significantly as was previously reported (Zeng et al, 2015).…”
Section: Effect Of Essential Oils On the In Vitro Growth Of Colletotrmentioning
confidence: 48%
“…Previous studies have shown a strong antagonistic activity of thyme essential oil against undesirable bacteria (Hosseini et al, 2009). However, it is shown that this is not the case with the fungus evaluated here, which could be explained due to when the thyme essential oil is mixed with Tween ® , then the antifungal capacity decreases significantly as was previously reported (Zeng et al, 2015).…”
Section: Effect Of Essential Oils On the In Vitro Growth Of Colletotrmentioning
confidence: 48%
“…The cells were dried at 60°C for 6 h and then at 40°C overnight, and weighed. Percent growth inhibition on the basis of dry weight was calculated as follows: (Control weight-Sample weight)/ Control weight × 100 [27]. All experiments were conducted in triplicate.…”
Section: Determination Of Biomassmentioning
confidence: 99%
“…Membrane damage was examined following the procedure described previously but with a slight modification [27]. Briefly, a single C. neoformans colony from an overnight SDA culture plate was inoculated into 60 mL of SDB containing different concentrations of the EO.…”
Section: Determination Of Ergosterol Content In the Plasma Membrane Omentioning
confidence: 99%
“…Throughout our study results, we found inhibition zone only against T. mentagrophytes and M. canis that might be more sensitive to fennel seeds essential oil than those of the other tested dermophytes. Zeng et al [37] showed that fennel seed essential oil could be used as a potential antidermatophytic agent. Ozcan et al [38] also reported that, the most affected fungus by the bitter fennel oil rich in estragole was Alternaria alternata followed by Fusarium oxysporum.…”
Section: Antifungal Activitymentioning
confidence: 99%